STRATEGIC PLAN FOR INTERNAL EMPLOYER BRANDING AT INDONESIA TELECOMMUNICATION COMPANY FOR THE PERIOD 2024-2025 - Ghaisani, Nurul; Saragih, Eva Hotnaidah (International Journal of Professional Business Review, 2024)
Purpose: Amidst ongoing changes, employer branding is crucial for attracting and retaining top talent. Given the competitive job market, it's essential to establish the company as an appealing workplace. This study aims to develop an internal employer branding strategy for Company for 2024-2025 by analyzing current practices and identifying key areas for improving the employee value proposition, ultimately enhancing the company's attractiveness to employees.